Relationship of Burnout With Personality, Alexithymia, and Coping Behaviors Among Physicians in A Semiurban and Rural Area in Turkey - Taycan, O.; Taycan S.E.; Celik C. (Taylor and Francis Inc., 2014)
This present study aimed to assess levels of burnout, to investigate the extent to which personal characteristics and coping behaviors are related to burnout, and to establish the predictors of burnout among physicians in a semiurban and rural area. A sample of 139 physicians was assessed using the Maslach Burnout Inventory, Eysenck Personality Questionnaire, Toronto Alexithymia Scale, and Ways of Coping Inventory. The level of burnout was found to be moderately higher than those reported among urban physicians. A forward stepwise multiple regression analysis indicated that neuroticism, occupation (specialist vs general practitioner), helpless, self-confident, and social support seeking approaches were predictors of burnout. The results showed that burnout was negatively related with problem-focused copping strategies, and positively with emotion-focused coping strategies. Fostering problem-focused coping strategies in physicians might be useful in the reduction of burnout. © 2014 Taylor & Francis Group, LLC.
PubMed ID: 24325746
Keywords: Alexithymia; Burnout; Coping behavior; Personality; Physicians